Investigating Shear Wave Physics in a Generic Pediatric Left Ventricular Model via In Vitro Experiments and Finite Element Simulations - Caenen, Annette; Pernot, Mathieu; Shcherbakova, Darya Alexandrovna; Mertens, Luc; Kersemans, Mathias; Segers, Patrick; Swillens, Abigail (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2017)
Shear wave elastography (SWE) is a potentially valuable tool to noninvasively assess ventricular function in children with cardiac disorders, which could help in the early detection of abnormalities in muscle characteristics. Initial experiments demonstrated the potential of this technique in measuring ventricular stiffness; however, its performance remains to be validated as complicated shear wave (SW) propagation characteristics are expected to arise due to the complex non-homogenous structure of the myocardium. In this work, we investigated the (i) accuracy of different shear modulus estimation techniques (time-of-flight (TOF) method and phase velocity analysis) across myocardial thickness and (ii) effect of the ventricular geometry, surroundings, acoustic loading, and material viscoelasticity on SW physics. A generic pediatric (10-15-year old) left ventricular model was studied numerically and experimentally. For the SWE experiments, a polyvinylalcohol replicate of the cardiac geometry was fabricated and SW acquisitions were performed on different ventricular areas using varying probe orientations. Additionally, the phantom's stiffness was obtained via mechanical tests. The results of the SWE experiments revealed the following trends for stiffness estimation across the phantom's thickness: a slight stiffness overestimation for phase speed analysis and a clear stiffness underestimation for the TOF method for all acquisitions. The computational model provided valuable 3-D insights in the physical factors influencing SW patterns, especially the surroundings (water), interface force, and viscoelasticity. In conclusion, this paper presents a validation study of two commonly used shear modulus estimators for different ventricular locations and the essential role of SW modeling in understanding SW physics in the pediatric myocardium.